Breast Diagnostic Tumor Using Compact Butterfly-Shaped Antenna Signals for Medical Sensor Applications - Hiwa Taha Sediq; Mohammad Fathi; Keyhan Hosseini; Bahman Mohammadi (Results in Engineering, 2025)
This manuscript discusses detecting breast cancers for early intervention and increasing the chances of saving the patient’s existence using a compact wideband Vivaldi antenna. The Vivaldi antenna has specific advantages such as wide bandwidth, high resolution, and non-invasive measurable nature, making it a promising tool for tumor detection in breast tissue. Therefore, a unique butterfly-shaped patch is used in the Vivaldi antenna to address the needs of contemporary wireless applications in this study. The broadband Vivaldi antenna has been printed on inexpensive substrate of FR4, which has the total surface area of 0.32λo x 0.32λo and an operating range of 2.64 to greater than 24 GHz. The butterfly-shaped antenna presents a distinctive design option for a number of applications, including those that operate at frequencies of UWB in 3.1–10.6 GHz range, WiMAX at 3.6 GHz, WLAN at 5.4GHz, X-band in 8–12 GHz range, Ku-band in 12–18 GHz range, k band, and spanning other frequency series. To distinguish malignant and healthy tissues using the dielectric contrast principle, microwave imaging systems are combined with the directional radiation pattern and high-frequency range of the Vivaldi antenna. The presence of tumors alters the dielectric properties of the medium in which the antenna operates, leading to disparities in the interaction of the electromagnetic waves that the antenna can detect. Based on numerical simulations and preliminary experimental results, it can be confirmed that the Vivaldi antenna can be used in microwave tomography for detection of breast cancer in a better manner with higher accuracy, lower false positive rates and providing high gain of 8.51dBi.